Keanekaragaman Genus Dan Pola Distribusi Semut (Formicidae) pada Areal Perkebunan Jabon Putih (Antocephaluscadamba (Roxb.) Miq.) di Desa Durian Kabupaten Kubu Raya - Linda, Adonovan Wulandari (Jurnal Protobiont, 2016)
White jabon (Anthochepaluscadamba) has high prospects for plantation forest and reforestation plants. Woody plants like white jabon (A. cadamba) are commonly used by ants for nesting. This research aims to find out the diversity of genera and distribution patterns of ants in the plantation area of white jabon (A. cadamba) in Sungai Durian Village, Sungai AmbawangSubdistrict. Data were collected through combined methods of transect and plot line in two sampling locations in the plantation area of white jabon (A. cadamba). The first location is a newly cleared land with jabon plants aged more or less 12 months. The second location is a previously horticultural farmland that was converted into agricultural farmland of jabon aged more or less 8 months. Samples of ants were collected with pitfall traps, bait traps, soil core sample and hand collecting. The results of sampling found 4 genera of ants i.e. Iridomyrmex, Solenopsis, DiacammaandMonomorium. Genus Iridomyrmex was a genus with most individuals (983 individuals) andMonomoriumsp was a genus with the fewest individuals (296 individuals). The index value of species diversity at both locations was low (Location 1 H '= 1.376 and Location 2 H' = 0.6843). The genus which dominates was not found and the condition of both locations was stable. Sorensen similarity index showed that both locations had a high similar genus (IS = 66.67%). All the ants had a clustered distribution patterns.